Analysis of the Effect of Innovative Work Behavior in terms of Psychological Empowerment and Knowledge Sharing - Simatupang, Sudung; Dharma, Edy; Ambarita, Marthin Hutler; Indajang, Kevin; Sudirman, Acai (International Journal of Scientific Research and Management (IJSRM), 2022)
Human resource development is part of management in organizing, directing, and leadership in an innovative organization. This is important to implement concerning the increasingly complex demands of work, the rapid progress of science and technology, and increasingly fierce global competition. Therefore, organizations need to study what factors influence innovative work behavior. This study examines the effect of psychological empowerment and knowledge sharing on innovative work behavior. The data collected in this study are quantitative data using an associative research design approach. The population in this study were private employees in Pematang Siantar City with a sample of 170 employees determined by purposive sampling method. Data analysis used instrument tests, normality tests, regression tests, hypothesis tests, correlation tests, and the coefficient of determination. The results showed that psychological empowerment and knowledge sharing positively and significantly affected innovative work behavior. The study's conclusion confirms that to improve innovative work behavior, organizations should pay attention to the psychological empowerment of each employee so that they feel that their work is meaningful and contributes significantly to organizational achievement. Furthermore, the importance of knowledge sharing for employees will be seen when they understand their job descriptions and exchange opinions regarding their work.